1979
DOI: 10.1021/ja00509a045
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of prostaglandin H2

Abstract: Prostaglandin H2 (PGFL) has been prepared by chemical synthesis from PGF;,,. The synthesis proceeds from the intermediate 9/3,1 l/3-dibromo-9,l 1-dideoxyprostaglandin F2iv to the endoperoxide PGFL in 17-24% yield upon reaction of the dibromide with silver trifluoroacetate and hydrogen peroxide in diethyl ether. Synthetic PGFL was purified by high-pressure liquid chromatography and was characterized by comparison with a biological sample and by conversion to PGF2" methyl ester, PGE2, and PGFL methyl ester under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

1981
1981
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 2 publications
0
8
0
3
Order By: Relevance
“…The following prostanoids were prepared in our laboratory and essential details of the synthetic methods are to be found in Wilson et al (1982Wilson et al ( , 1988: rac 10a-homo-15S-hydroxy-9a, La-epoxy-prosta-5Z,13E-dienoic acid (9,1 1-endoxy-lOa-homo PGH2) and its 16p-fluorophenoxy-w)-tetranor (EP 171) and 13-(m-chlorobenzyloxyimino)-w)-heptanor (EP 204) analogues; rac 9a,1 aethanocoheptanor -13 -methyl -13 -phenylthio-carbamoyl-hydrazino-prosta-5Z-enoic acid (EP 092); 1 lacarba -i5S -hydroxy -9a,1 laisopropylidenoprosta -5Z,13Edienoic acid (PTA2) and its 16p-fluorophenoxy-w)-tetranor (EP 109), wo-heptanor-13-methyl-13-phenylecarbamoylhydrazino (EP 115) and 16,20-methano (16,20-methano PTA2) analogues; 9a,1 lc-ethano-w-heptanor-lOa-homo-13-(m-chlorobenzyl-oxyimino)prosta-5Z-enoic acid (EP 167) and 4a,10adihomo -9a,1 lethanocoheptanor -3 -oxa -13 -phenylthiocarbamoyl-hydrazino-prostanoic acid (EP 169); 16-pfluorophenoxy-w-tetranor PGF2,. PGH2 was prepared from PGF2, by the method of Porter et al (1979).…”
Section: Compoundsmentioning
confidence: 99%
“…The following prostanoids were prepared in our laboratory and essential details of the synthetic methods are to be found in Wilson et al (1982Wilson et al ( , 1988: rac 10a-homo-15S-hydroxy-9a, La-epoxy-prosta-5Z,13E-dienoic acid (9,1 1-endoxy-lOa-homo PGH2) and its 16p-fluorophenoxy-w)-tetranor (EP 171) and 13-(m-chlorobenzyloxyimino)-w)-heptanor (EP 204) analogues; rac 9a,1 aethanocoheptanor -13 -methyl -13 -phenylthio-carbamoyl-hydrazino-prosta-5Z-enoic acid (EP 092); 1 lacarba -i5S -hydroxy -9a,1 laisopropylidenoprosta -5Z,13Edienoic acid (PTA2) and its 16p-fluorophenoxy-w)-tetranor (EP 109), wo-heptanor-13-methyl-13-phenylecarbamoylhydrazino (EP 115) and 16,20-methano (16,20-methano PTA2) analogues; 9a,1 lc-ethano-w-heptanor-lOa-homo-13-(m-chlorobenzyl-oxyimino)prosta-5Z-enoic acid (EP 167) and 4a,10adihomo -9a,1 lethanocoheptanor -3 -oxa -13 -phenylthiocarbamoyl-hydrazino-prostanoic acid (EP 169); 16-pfluorophenoxy-w-tetranor PGF2,. PGH2 was prepared from PGF2, by the method of Porter et al (1979).…”
Section: Compoundsmentioning
confidence: 99%
“…Displacement by synthetic PGH2 and by TXA2 generated enzymatically from synthetic PGH2 was also studied. PGF2o, was converted into 93,1 113dibromo-9, 11 -dideoxy PGF2, by the method of Porter, Byers, Holden & Menzel (1979). Treatment of the dibromo derivative with 90% H202/silver trifluoroacetate gave PGH2 which was purified by silicic acid chromatography (10g Unisil, 100-200 mesh Clarkson Chemical Co., USA; gradient elution, 20% ethyl acetate in hexane to pure ethyl acetate over 3 h; -20°C).…”
Section: Binding Studiesmentioning
confidence: 99%
“…PGF2o, was converted into 93,1 113-dibromo-9, 11 -dideoxy PGF2, by the method of Porter, Byers, Holden & Menzel (1979 , and incubated for 30 s at 0°C. The suspension was filtered rapidly at 0°C under pressure from a nitrogen gas cylinder through an Amicon MPS-1 micropartition unit (Amicon Ltd, Stonehouse).…”
Section: Introductionmentioning
confidence: 99%
“…[58b] Subsequently, Porter et al showed that isolated PGH 2 rearranges spontaneously in the presence of silica gel to a mixture of PGE 2 and PGD 2 . [62] However, acid-base catalysis also leads to the formation of PGD 2 or PGE 2 . [63] It is noteworthy that 15-E 2 -and 15-D 2 -IsoP (15-45 b and 15-46 b, respectively) epimerize in aqueous solution at pH 7.4 to a 4.5:1 equilibrium mixture of thermodynamically more stable, but racemic rac-PGD 2 and rac-PGE 2 diastereomers.…”
Section: Isoprostanesmentioning
confidence: 99%